A high-energy-density lithium-ion battery, an electrolyte and a preparation method thereof

CN123018125APending Publication Date: 2026-10-30CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611112710.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-25
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]为了解决现有技术中“锂离子电池性能的提升正日益受到正极活性材料质量负载极限的严重制约,单纯依靠增加电极厚度或优化传统正极材料已难以满足日益增长的高能量密度需求”的问题,本发明的目的在于提供一种高能量密度的锂离子电池、电解液及其制备方法,创造性地利用充放电过程中产生的还原性金属离子作为“催化剂”,主动诱导并调控锂盐阴离子的氧化还原反应,提供了一种突破现有锂离子电池能量密度瓶颈的创新策略

Benefits of technology

[0026](1)本发明并非依赖于提升正极活性材料的质量负载(这会导致动力学恶化),而是在现有或适度优化的电极结构基础上,从电解液组分中“挖掘”出额外的、可观的容量来源。锂盐阴离子的参与贡献了超越正极材料本身理论极限的电荷存储能力,显著提升了电池的整体比容量和能量密度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018125A_ABST
    Figure CN123018125A_ABST
Patent Text Reader

Abstract

The application discloses a high-energy-density lithium ion battery, an electrolyte and a preparation method thereof. The high-energy-density lithium ion battery comprises a positive electrode, a negative electrode, a diaphragm and an electrolyte. The electrolyte comprises a redox active lithium salt and an aprotic polar solvent. In the charging and discharging process, the reduction metal ions released by the positive electrode accurately trigger the reversible redox reaction of the anion of the redox active lithium salt in the electrolyte. The application creatively uses the reduction metal ions generated in the charging and discharging process as a 'catalyst' to actively induce and regulate the redox reaction of the lithium salt anion, providing an innovative strategy to break through the energy density bottleneck of the existing lithium ion battery, thereby solving the problem that the performance improvement of the lithium ion battery is increasingly restricted by the positive active material mass loading limit, and it is difficult to meet the increasing demand for high energy density by simply increasing the electrode thickness or optimizing the traditional positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of secondary battery technology, and in particular to a high-energy-density lithium-ion battery, an electrolyte, and a method for preparing the same. Background Technology

[0002] In recent years, with the urgent global demand for clean energy, sustainable transportation, and portable electronic devices, lithium-ion batteries have become an indispensable key energy storage technology supporting modern societal development due to their advantages such as high energy density, long cycle life, and low self-discharge rate. Their widespread application in electric vehicles (EVs), hybrid electric vehicles (HEVs / PHEVs), large-scale grid energy storage systems, and consumer electronics such as smartphones and laptops has driven the continuous pursuit of higher-performance lithium-ion batteries.

[0003] In lithium-ion batteries, the cathode material is one of the key factors determining its energy density. Currently, the theoretical and achievable specific capacities of mainstream commercially available cathode materials (such as lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), and ternary materials NMC / NCA) are gradually approaching their physicochemical limits. To store more energy within a single volume, a direct strategy is to increase the mass loading of the active material in the electrode (the mass of active material per unit area of ​​the electrode) or to fabricate a thicker electrode. However, this strategy faces significant technical challenges: as the thickness of the active material layer or the loading increases, the ion and electron transport impedance within the electrode increases significantly. This leads to slower electrode reaction kinetics, increased polarization, and decreased utilization of the active material. Especially under high-rate charge-discharge conditions, the battery capacity not only fails to increase linearly but may even deteriorate. Furthermore, thick electrodes are prone to stress accumulation, cracking, and delamination from the current collector during cycling, affecting the battery's cycle stability and safety. Therefore, the limitation of the mass loading of the cathode active material has become one of the main bottlenecks for further improving the energy density of lithium-ion batteries. Summary of the Invention

[0004] To address the problem that "the improvement of lithium-ion battery performance is increasingly constrained by the mass load limit of the positive electrode active material, and simply increasing the electrode thickness or optimizing traditional positive electrode materials is no longer sufficient to meet the growing demand for high energy density," the present invention aims to provide a high-energy-density lithium-ion battery, electrolyte, and preparation method thereof. It creatively utilizes the reducing metal ions generated during charging and discharging as a "catalyst" to actively induce and regulate the redox reaction of lithium salt anions, providing an innovative strategy to break through the energy density bottleneck of existing lithium-ion batteries.

[0005] To achieve the above objectives, the present invention provides the following technical solution:

[0006] In a first aspect, the present invention provides a high-energy-density lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte;

[0007] The electrolyte comprises redox-active lithium salts and aprotic polar solvents;

[0008] During charging and discharging, the reducing metal ions released from the positive electrode precisely trigger a reversible redox reaction between the anions of the redox-active lithium salt in the electrolyte.

[0009] In a preferred embodiment, the active material of the positive electrode is lithium iron phosphate (LiFePO4) or lithium manganese iron phosphate (LiMn). x Fe 1- x PO4), lithium cobalt oxide (LiCoO2), spinel lithium nickel manganese oxide (LiNi) 0.5 Mn 1.5 O4), lithium nickel cobalt manganese oxide (LiNi) x Co y Mn z O2) and lithium nickel cobalt aluminum oxide (LiNi x Co y Al z At least one of O2).

[0010] Furthermore, the reducing metal ions include Fe. 2+ Mn 2+ Co 2+ Ni 2+ At least one of them.

[0011] In a preferred embodiment, the redox-active lithium salt includes at least one of lithium nitrate (LiNO3), lithium persulfate (Li2S2O8), lithium bromate (LiBrO3), lithium chlorate (LiClO3), and lithium chlorite (LiClO2).

[0012] In a preferred embodiment, the aprotic polar solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), ethylene glycol dimethyl ether (DME), tetrahydrofuran (THF), diethylene glycol dimethyl ether (DEGDME), tetraethylene glycol dimethyl ether (TEGDME), dioxolane (DOL), acetonitrile (ACN), sulfolane (TMS), and dimethyl sulfoxide (DMSO).

[0013] In a preferred embodiment, the negative electrode is metallic lithium or a lithium alloy.

[0014] In a preferred embodiment, the diaphragm is a glass fiber diaphragm.

[0015] In a second aspect, the present invention also provides a high-energy-density electrolyte for lithium-ion batteries, comprising a redox-active lithium salt and an aprotic polar solvent, wherein the redox-active lithium salt accounts for 10% to 30% of the total mass of the electrolyte, and the aprotic polar solvent accounts for 70% to 90% of the total mass of the electrolyte;

[0016] The redox active lithium salt includes at least one of lithium nitrate (LiNO3), lithium persulfate (Li2S2O8), lithium bromate (LiBrO3), lithium chlorate (LiClO3), and lithium chlorite (LiClO2);

[0017] The aprotic polar solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), ethylene glycol dimethyl ether (DME), tetrahydrofuran (THF), diethylene glycol dimethyl ether (DEGDME), tetraethylene glycol dimethyl ether (TEGDME), dioxolane (DOL), acetonitrile (ACN), sulfolane (TMS), and dimethyl sulfoxide (DMSO).

[0018] Furthermore, the redox active lithium salt is at least one of lithium nitrate (LiNO3) and lithium persulfate (Li2S2O8), and its mass percentage is 15% to 25%.

[0019] Furthermore, the aprotic polar solvent is at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), ethylene glycol dimethyl ether (DME), and dimethyl sulfoxide (DMSO), and accounts for 75% to 85% by mass.

[0020] Thirdly, the present invention also provides a method for preparing the electrolyte, comprising:

[0021] Under an inert atmosphere, redox active lithium salt and aprotic polar solvent are mixed at a mass ratio of 10~30 : 70~90; and stirred at 10~60℃ for 2~24 hours until completely dissolved.

[0022] In some specific embodiments, the inert atmosphere is argon or nitrogen, the stirring temperature is preferably 25~40℃, and the stirring time is preferably 6~12 hours.

[0023] This invention designs a specific electrolyte system that serves not only as an ion transport medium but also as an active material, overcoming the limitations of active materials in electrodes and significantly improving battery capacity. During battery charging and discharging, the anions of the redox active lithium salt are reduced by reducing metal ions (such as Fe) at the positive electrode. 2+ Mn2+ Co 2+ Ni 2+ The lithium salt anions in the electrolyte undergo further reaction under the catalytic action of the electrolyte components (lithium salt anions). This reaction is not a simple side reaction that consumes lithium; rather, it is designed to purposefully promote a reversible redox reaction of lithium salt anions in the electrolyte. This redox process, based on the participation of electrolyte components (lithium salt anions), provides a novel and promising technical route for achieving a substantial increase in the capacity of lithium-ion batteries. The reaction formula involved is as follows (using LiFePO4 as an example): first step:

[0024] Step Two:

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] (1) This invention does not rely on increasing the mass loading of the positive electrode active material (which would lead to kinetic degradation), but rather on “mining” additional and considerable capacity sources from the electrolyte composition based on existing or moderately optimized electrode structures. The participation of lithium salt anions contributes to charge storage capacity that exceeds the theoretical limit of the positive electrode material itself, significantly improving the overall specific capacity and energy density of the battery.

[0027] (2) Compared with simply pursuing the development of new high-capacity cathode materials or complex electrode structures (which are often accompanied by problems such as high cost, complex process and poor stability), this invention provides a novel and efficient technical route to achieve capacity leap through the functional design of electrolyte components, which expands the dimensions of lithium-ion battery capacity improvement.

[0028] (3) This invention provides an innovative strategy to break through the energy density bottleneck of existing lithium-ion batteries. Theoretically, this strategy can be applied to various cathode systems containing easily soluble transition metals (such as Mn, Fe, Co, Ni, etc.) (such as lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, high-nickel ternary, lithium-rich manganese-based, etc.), and has good compatibility and application potential. If the stabilization and efficiency of this electrolyte system can be successfully achieved, it is expected to provide strong technical support for the development of next-generation high-energy-density lithium-ion batteries, and has significant practical significance for promoting long-range electric vehicles, miniaturization and long standby time of portable electronic devices, and cost reduction and efficiency improvement of large-scale energy storage systems. Attached Figure Description

[0029] Figure 1 The image shows the charge-discharge curves of the lithium-ion battery assembled in Example 1.

[0030] Figure 2 The graph shows the specific capacity cycling performance of the lithium-ion battery assembled in Example 1.

[0031] Figure 3 The graph shows the specific energy cycling performance of the lithium-ion battery assembled in Example 1. Detailed Implementation

[0032] The specific embodiments of the present invention will now be clearly and completely described in conjunction with the accompanying drawings.

[0033] Obviously, the described embodiments are only used to explain the present invention and are not intended to limit the present invention. Any non-essential changes and adjustments made by those skilled in the art based on the content of the present invention shall fall within the protection scope of the present invention.

[0034] The present invention will be further described below with reference to specific embodiments and accompanying drawings.

[0035] Example 1

[0036] In an argon-filled glove box, weigh redox active lithium salt and organic solvent (LiNO3: EC = 1:4 mass ratio), and stir at 25°C for 12 hours to fully dissolve them, thus obtaining a high-energy-density electrolyte for lithium-ion batteries.

[0037] Under an argon atmosphere, CR2032 coin cells were assembled using lithium iron phosphate as the positive electrode, glass fiber as the separator, and lithium metal as the negative electrode, and then electrolyte was injected. The battery cycle stability test procedure was set to capacity cutoff.

[0038] The positive electrode sheet is prepared by the following steps: lithium iron phosphate, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 8:1:1; N-methylpyrrolidone solvent is added and the mixture is ground into a slurry; the slurry is coated onto an aluminum foil current collector and dried under vacuum at 120°C for 12 hours before being sliced.

[0039] Example 2

[0040] In an argon-filled glove box, weigh redox active lithium salt and organic solvent (electrolyte: LiNO3:DMC = 1:4 mass ratio), and stir at 25°C for 12 hours to fully dissolve them, thus obtaining a high-energy-density electrolyte for lithium-ion batteries.

[0041] Under an argon atmosphere, CR2032 coin cells were assembled using lithium iron phosphate as the positive electrode, glass fiber as the separator, and lithium metal as the negative electrode, and then electrolyte was injected. The battery cycle stability test procedure was set to capacity cutoff.

[0042] The positive electrode sheet is prepared by the following steps: lithium iron phosphate, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 8:1:1; N-methylpyrrolidone solvent is added and the mixture is ground into a slurry; the slurry is coated onto an aluminum foil current collector and dried under vacuum at 120°C for 12 hours before being sliced.

[0043] Example 3

[0044] In an argon-filled glove box, weigh redox active lithium salt and organic solvent (electrolyte:LiNO3:DME=1:4 mass ratio), and stir at 25℃ for 12h to fully dissolve them, thus obtaining a high-energy-density lithium-ion battery electrolyte.

[0045] Under an argon atmosphere, CR2032 coin cells were assembled using lithium iron phosphate as the positive electrode, glass fiber as the separator, and lithium metal as the negative electrode, and then electrolyte was injected. The battery cycle stability test procedure was set to capacity cutoff.

[0046] The positive electrode sheet is prepared by the following steps: lithium iron phosphate, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 8:1:1; N-methylpyrrolidone solvent is added and the mixture is ground into a slurry; the slurry is coated onto an aluminum foil current collector and dried under vacuum at 120°C for 12 hours before being sliced.

[0047] Example 4

[0048] In an argon-filled glove box, weigh redox active lithium salt and organic solvent (electrolyte:LiNO3:DMSO=1:4 mass ratio), and stir at 25℃ for 12h to fully dissolve them, thus obtaining a high-energy-density lithium-ion battery electrolyte.

[0049] Under an argon atmosphere, CR2032 coin cells were assembled using lithium iron phosphate as the positive electrode, glass fiber as the separator, and lithium metal as the negative electrode, and then electrolyte was injected. The battery cycle stability test procedure was set to capacity cutoff.

[0050] The positive electrode sheet is prepared by the following steps: lithium iron phosphate, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 8:1:1; N-methylpyrrolidone solvent is added and the mixture is ground into a slurry; the slurry is coated onto an aluminum foil current collector and dried under vacuum at 120°C for 12 hours before being sliced.

[0051] Example 5

[0052] In an argon-filled glove box, weigh redox active lithium salt and organic solvent (electrolyte: Li2S2O8 : DMC = 1:4 by mass), and stir at 25°C for 12 hours to fully dissolve them, thus obtaining a high-energy-density electrolyte for lithium-ion batteries.

[0053] Under an argon atmosphere, CR2032 coin cells were assembled using lithium iron phosphate as the positive electrode, glass fiber as the separator, and lithium metal as the negative electrode, and then electrolyte was injected. The battery cycle stability test procedure was set to capacity cutoff.

[0054] The positive electrode sheet is prepared by the following steps: lithium iron phosphate, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 8:1:1; N-methylpyrrolidone solvent is added and the mixture is ground into a slurry; the slurry is coated onto an aluminum foil current collector and dried under vacuum at 120°C for 12 hours before being sliced.

[0055] Example 6

[0056] In an argon-filled glove box, weigh redox active lithium salt and organic solvent (electrolyte: Li2S2O8 : DME = 1:4 mass ratio), stir at 25°C for 12 h to fully dissolve, thus obtaining a high-energy-density lithium-ion battery electrolyte.

[0057] Under an argon atmosphere, CR2032 coin cells were assembled using lithium iron phosphate as the positive electrode, glass fiber as the separator, and lithium metal as the negative electrode, and then electrolyte was injected. The battery cycle stability test procedure was set to capacity cutoff.

[0058] The positive electrode sheet is prepared by the following steps: lithium iron phosphate, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 8:1:1; N-methylpyrrolidone solvent is added and the mixture is ground into a slurry; the slurry is coated onto an aluminum foil current collector and dried under vacuum at 120°C for 12 hours before being sliced.

[0059] Example 7

[0060] In an argon-filled glove box, weigh redox active lithium salt and organic solvent (electrolyte is Li2S2O8:DMSO = 1:4 mass ratio), stir at 25℃ for 12h to fully dissolve, and obtain high energy density lithium-ion battery electrolyte.

[0061] Under an argon atmosphere, CR2032 coin cells were assembled using lithium iron phosphate as the positive electrode, glass fiber as the separator, and lithium metal as the negative electrode, and then electrolyte was injected. The battery cycle stability test procedure was set to capacity cutoff.

[0062] The positive electrode sheet is prepared by the following steps: lithium iron phosphate, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 8:1:1; N-methylpyrrolidone solvent is added and the mixture is ground into a slurry; the slurry is coated onto an aluminum foil current collector and dried under vacuum at 120°C for 12 hours before being sliced.

[0063] Example 8

[0064] In an argon-filled glove box, weigh redox active lithium salt and organic solvent (electrolyte: LiNO3: EC = 1:4 mass ratio), and stir at 25°C for 12 hours to fully dissolve them, thus obtaining a high-energy-density electrolyte for lithium-ion batteries.

[0065] Under an argon atmosphere, CR2032 coin cells were assembled using lithium manganese iron phosphate as the positive electrode, glass fiber as the separator, and lithium metal as the negative electrode, followed by the injection of electrolyte. The battery cycle stability test procedure was set to capacity cutoff.

[0066] The positive electrode sheet is prepared by the following steps: lithium manganese iron phosphate, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 8:1:1; N-methylpyrrolidone solvent is added and ground into a slurry; the slurry is coated onto an aluminum foil current collector, vacuum dried at 120°C for 12 hours, and then sliced.

[0067] Example 9

[0068] In an argon-filled glove box, weigh redox active lithium salt and organic solvent (electrolyte: LiNO3:DMC = 1:4 mass ratio), and stir at 25°C for 12 hours to fully dissolve them, thus obtaining a high-energy-density electrolyte for lithium-ion batteries.

[0069] Under an argon atmosphere, CR2032 coin cells were assembled using lithium manganese iron phosphate as the positive electrode, glass fiber as the separator, and lithium metal as the negative electrode, followed by the injection of electrolyte. The battery cycle stability test procedure was set to capacity cutoff.

[0070] The positive electrode sheet is prepared by the following steps: lithium manganese iron phosphate, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 8:1:1; N-methylpyrrolidone solvent is added and ground into a slurry; the slurry is coated onto an aluminum foil current collector, vacuum dried at 120°C for 12 hours, and then sliced.

[0071] Example 10

[0072] In an argon-filled glove box, weigh redox active lithium salt and organic solvent (electrolyte: LiNO3 : DME = 1:4 mass ratio), and stir at 25°C for 12 hours to fully dissolve them, thus obtaining a high-energy-density lithium-ion battery electrolyte.

[0073] Under an argon atmosphere, a CR2032 coin cell was assembled using lithium manganese iron phosphate as the positive electrode, glass fiber as the separator, and lithium metal sheets as the negative electrode, followed by the injection of electrolyte. The battery cycle stability test procedure was set to capacity cutoff.

[0074] The positive electrode sheet is prepared by the following steps: lithium manganese iron phosphate, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 8:1:1; N-methylpyrrolidone solvent is added and ground into a slurry; the slurry is coated onto an aluminum foil current collector, vacuum dried at 120°C for 12 hours, and then sliced.

[0075] Example 11

[0076] In an argon-filled glove box, weigh redox active lithium salt and organic solvent (electrolyte:LiNO3:DMSO=1:4 mass ratio), and stir at 25℃ for 12h to fully dissolve them, thus obtaining a high-energy-density lithium-ion battery electrolyte.

[0077] Under an argon atmosphere, a CR2032 coin cell was assembled using lithium manganese iron phosphate as the positive electrode, glass fiber as the separator, and lithium metal sheets as the negative electrode, followed by the injection of electrolyte. The battery cycle stability test procedure was set to capacity cutoff.

[0078] The positive electrode sheet is prepared by the following steps: lithium manganese iron phosphate, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 8:1:1; N-methylpyrrolidone solvent is added and ground into a slurry; the slurry is coated onto an aluminum foil current collector, vacuum dried at 120°C for 12 hours, and then sliced.

[0079] Example 12

[0080] In an argon-filled glove box, weigh redox active lithium salt and organic solvent (electrolyte: Li2S2O8 : DMC = 1:4 mass ratio), stir at 25°C for 12 h to fully dissolve, thus obtaining a high-energy-density lithium-ion battery electrolyte.

[0081] Under an argon atmosphere, CR2032 coin cells were assembled using lithium manganese iron phosphate as the positive electrode, glass fiber as the separator, and lithium metal as the negative electrode, followed by the injection of electrolyte. The battery cycle stability test procedure was set to capacity cutoff.

[0082] The positive electrode sheet is prepared by the following steps: lithium manganese iron phosphate, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 8:1:1; N-methylpyrrolidone solvent is added and ground into a slurry; the slurry is coated onto an aluminum foil current collector, vacuum dried at 120°C for 12 hours, and then sliced.

[0083] Example 13

[0084] In an argon-filled glove box, weigh redox active lithium salt and organic solvent (electrolyte with a mass ratio of Li2S2O8:DME = 1:4), and stir at 25°C for 12 hours to fully dissolve them, thus obtaining a high-energy-density electrolyte for lithium-ion batteries.

[0085] Under an argon atmosphere, a CR2032 coin cell was assembled using lithium manganese iron phosphate as the positive electrode, glass fiber as the separator, and lithium metal sheets as the negative electrode, followed by the injection of electrolyte. The battery cycle stability test procedure was set to capacity cutoff.

[0086] The positive electrode sheet is prepared by the following steps: lithium manganese iron phosphate, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 8:1:1; N-methylpyrrolidone solvent is added and ground into a slurry; the slurry is coated onto an aluminum foil current collector, vacuum dried at 120°C for 12 hours, and then sliced.

[0087] Example 14

[0088] In an argon-filled glove box, weigh redox active lithium salt and organic solvent (electrolyte is Li2S2O8:DMSO = 1:4 mass ratio), stir at 25℃ for 12h to fully dissolve, and obtain high energy density lithium-ion battery electrolyte.

[0089] Under an argon atmosphere, a CR2032 coin cell was assembled using lithium manganese iron phosphate as the positive electrode, glass fiber as the separator, and lithium metal sheets as the negative electrode, followed by the injection of electrolyte. The battery cycle stability test procedure was set to capacity cutoff.

[0090] The positive electrode sheet is prepared by the following steps: lithium manganese iron phosphate, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 8:1:1; N-methylpyrrolidone solvent is added and ground into a slurry; the slurry is coated onto an aluminum foil current collector, vacuum dried at 120°C for 12 hours, and then sliced.

[0091] Comparative Example 1

[0092] In an argon-atmosphere glove box, CR2032 coin cells were assembled using lithium iron phosphate as the positive electrode, glass fiber as the separator, 1M LiPF6 in 30wt%EC+40wt%DMC+30wt%EMC as the electrolyte, and lithium metal as the negative electrode. The electrolyte was then injected. The battery cycle stability test procedure was set to capacity cutoff.

[0093] The positive electrode sheet is prepared by the following steps: lithium iron phosphate, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 8:1:1; N-methylpyrrolidone solvent is added and the mixture is ground into a slurry; the slurry is coated onto an aluminum foil current collector and dried under vacuum at 120°C for 12 hours before being sliced.

[0094] Comparative Example 2

[0095] In an argon-atmospheric glove box, CR2032 coin cells were assembled using lithium iron phosphate as the positive electrode, glass fiber as the separator, LiPF6:EC (mass ratio) as the electrolyte (1:4 mass ratio), and lithium metal as the negative electrode. The electrolyte was then injected. The battery cycle stability test procedure was set to capacity cutoff.

[0096] The positive electrode sheet is prepared by the following steps: lithium iron phosphate, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 8:1:1; N-methylpyrrolidone solvent is added and the mixture is ground into a slurry; the slurry is coated onto an aluminum foil current collector and dried under vacuum at 120°C for 12 hours before being sliced.

[0097] Table 1 shows the results at 20 mA g in each embodiment. -1 At a current of 220 mAh g -1 The electrochemical performance tests conducted at capacity cutoff are shown in Table 1 below:

[0098] In the first step of the reaction, the theoretical capacity of lithium iron phosphate is 170 mAh / g (1C), while in the second step, the active substance NO3... - Convert to NO2 - This step can release a specific capacity of about 15000mAh / g. However, it takes a long time to complete one cycle and has a short lifespan. Therefore, the capacity cutoff method is used for battery testing to control the discharge specific capacity to be consistent (220mAh / g).

[0099] Table 1 Electrochemical performance of lithium batteries obtained in Examples 1-14 and Comparative Examples 1-2 Example 1 220 645.33 89.98 Example 2 220 644.15 88.76 Example 3 220 643.86 88.68 Example 4 220 640.62 93.43 Example 5 220 646.99 86.66 Example 6 220 635.14 89.12 Example 7 220 641.17 92.43 Example 8 220 657.96 90.67 Example 9 220 658.70 91.07 Example 10 220 653.86 90.47 Example 11 220 657.88 92.34 Example 12 220 654.34 90.45 Example 13 220 661.84 90.90 Example 14 220 655.33 91.66 Comparative Example 1 156 499.03 99.91 Comparative Example 2 149 476.21 98.67

[0100] This invention is the first to propose a synergistic mechanism between the anion redox activity design of the electrolyte and the catalytic action of the cathode metal ions, constructing an electrolyte system that combines both ion transport and capacity contribution functions. Its core innovation lies in the reducing metal ions (such as Fe) released by the cathode active material during charging and discharging. 2+ Mn 2+ Co 2+ Ni 2+ ), precisely triggering lithium salt anions (such as NO3) in the electrolyte - S2O8 2- A reversible redox reaction occurs, transforming the electrolyte from a traditional ionic conductor into a novel carrier of active materials. Compared to traditional electrolytes, this "two birds with one stone" functional electrolyte simultaneously solves the electrode load bottleneck, avoids the kinetic degradation caused by thicker electrodes, and breaks through the intrinsic specific capacity limit of cathode materials. This technology provides a completely new electrolyte design paradigm for high-energy-density lithium-ion batteries and can be widely used in power batteries, energy storage systems, and consumer electronics.

[0101] To ensure that the above description is merely a preferred embodiment of the present invention and only describes the implementation of the present invention, it is not intended to limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention's specification and drawings under the technical concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.

Claims

1. A high-energy-density lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, characterized in that, The electrolyte comprises redox-active lithium salts and aprotic polar solvents; During charging and discharging, the reducing metal ions released from the positive electrode precisely trigger a reversible redox reaction between the anions of the redox-active lithium salt in the electrolyte.

2. The high energy density lithium-ion battery according to claim 1, characterized in that, The active material of the positive electrode is lithium iron phosphate (LiFePO4) or lithium manganese iron phosphate (LiMn). x Fe 1-x PO4), lithium cobalt oxide (LiCoO2), spinel lithium nickel manganese oxide (LiNi) 0.5 Mn 1.5 O4), lithium nickel cobalt manganese oxide (LiNi) x Co y Mn z O2) and lithium nickel cobalt aluminum oxide (LiNi x Co y Al z At least one of O2).

3. The high energy density lithium-ion battery according to claim 1, characterized in that, The redox active lithium salt includes at least one of lithium nitrate (LiNO3), lithium persulfate (Li2S2O8), lithium bromate (LiBrO3), lithium chlorate (LiClO3), and lithium chlorite (LiClO2); The aprotic polar solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), ethylene glycol dimethyl ether (DME), tetrahydrofuran (THF), diethylene glycol dimethyl ether (DEGDME), tetraethylene glycol dimethyl ether (TEGDME), dioxolane (DOL), acetonitrile (ACN), sulfolane (TMS), and dimethyl sulfoxide (DMSO).

4. A high-energy-density lithium-ion battery according to claim 1, characterized in that, The negative electrode is metallic lithium or a lithium alloy.

5. A high-energy-density lithium-ion battery according to claim 1, characterized in that, The diaphragm is a glass fiber diaphragm.

6. A high-energy-density electrolyte for lithium-ion batteries, characterized in that, It includes redox-active lithium salts and aprotic polar solvents, with redox-active lithium salts accounting for 10% to 30% of the total mass of the electrolyte and aprotic polar solvents accounting for 70% to 90% of the total mass of the electrolyte; The redox active lithium salt includes at least one of lithium nitrate (LiNO3), lithium persulfate (Li2S2O8), lithium bromate (LiBrO3), lithium chlorate (LiClO3), and lithium chlorite (LiClO2); The aprotic polar solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), ethylene glycol dimethyl ether (DME), tetrahydrofuran (THF), diethylene glycol dimethyl ether (DEGDME), tetraethylene glycol dimethyl ether (TEGDME), dioxolane (DOL), acetonitrile (ACN), sulfolane (TMS), and dimethyl sulfoxide (DMSO).

7. The high-energy-density electrolyte for lithium-ion batteries according to claim 6, characterized in that, The redox active lithium salt is at least one of lithium nitrate (LiNO3) and lithium persulfate (Li2S2O8), and its mass percentage is 15% to 25%.

8. The high-energy-density electrolyte for lithium-ion batteries according to claim 6, characterized in that, The aprotic polar solvent is at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), ethylene glycol dimethyl ether (DME), and dimethyl sulfoxide (DMSO), and accounts for 75% to 85% by mass.

9. The method for preparing the electrolyte according to any one of claims 6 to 8, characterized in that, include: Under an inert atmosphere, redox active lithium salt and aprotic polar solvent are mixed at a mass ratio of 10~30 : 70~90; and stirred at 10~60℃ for 2~24 hours until completely dissolved.

10. The method for preparing the electrolyte according to claim 9, characterized in that, The inert atmosphere is argon or nitrogen, the stirring temperature is 25~40℃, and the stirring time is 6~12 hours.